ExomiRs: A Novel Strategy in Cancer Diagnosis and Therapy - Gorji-Bahri, Gilar; Hashemi, Atieh; Moghimi, Hamid R. (Current Gene Therapy, 2018)
Exosomes play a critical role in intercellular communication between cancer cells and their environments. These secreted nanovesicles can transfer different cargos such as mRNAs, proteins and microRNA (miRNA) to recipient cells. Exosomal miRNAs (exomiRs) derived from tumor cells have emerged as key players in cancer promotion via impairment of the immune system response, tumor growth, metastasis, angiogenesis, and chemotherapeutic drug resistance. Moreover, since dysregulation of miRNA expression in tumor cells can be reflected by distinct profiles of exomiRs extracted from the bodily fluids of cancer patients, they can be considered as non-invasive diagnostic, prognostic and predictive biomarkers. Additionally, due to the critical roles of exomiRs in cancer promotion, targeting of various aspects of exosome biogenesis, miRNA sorting or loading has been suggested as a novel approach for cancer therapy. Firstly, this review aims to describe the biosynthesis and trafficking of exosomes as well as their isolation, characterization and content. Next, the recent advances on the role of exomiRs in cancer promotion as well as the application of exomiR as a cancer biomarker and therapeutic target are reviewed.
Keywords: exomiRs